2017
DOI: 10.5603/fm.a2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

The expression of inhibitor of nuclear factor kappa-B kinase epsilon (IKKe) in human aortic aneurysm

Abstract: (Folia Morphol 2017; 76, 3: 372-378)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Therefore, it was inferred that IKKε plays an important role in AAA development. A previous study revealed that IKKε expression is significantly increased in patients with AAA ( 10 ). The results of a another study indicated that the lack of IKKε reduced AAA formation by reducing apoptosis and inflammation in the abdominal aorta of mice ( 11 ).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, it was inferred that IKKε plays an important role in AAA development. A previous study revealed that IKKε expression is significantly increased in patients with AAA ( 10 ). The results of a another study indicated that the lack of IKKε reduced AAA formation by reducing apoptosis and inflammation in the abdominal aorta of mice ( 11 ).…”
Section: Introductionmentioning
confidence: 97%
“…TAA, in addition to conventional risk factors, exhibits a strong heritable pattern [3]. Existing evidences show that AAA and TAA share similarities in pathological states and histological phenotypes, including inflammatory reaction and extracellular matrix (ECM) degeneration in aortic wall [4,5].…”
Section: Introductionmentioning
confidence: 99%